Liposome encapsulation of anionic and cationic whey peptides: Influence of peptide net charge on properties of the nanovesicles. (January 2018) - Mohan, Aishwarya; Rajendran, Subin R.C.K.; Thibodeau, Jacinthe; Bazinet, Laurent; Udenigwe, Chibuike C.
Abstract: Poor bioavailability of food-derived bioactive peptides impedes their application in functional foods. This study focuses on understanding the impact of net charge of whey peptides, separated by electrodialysis with ultrafiltration membrane (EDUF), on encapsulation efficiency (EE) and surface properties of the peptide-loaded liposomes. EDUF resulted in two fractions; anionic whey peptides (AWP) with a relative abundance of 30.4% anionic amino acid residues, and cationic whey peptides (CWP) with 20.39% cationic amino acid residues. Although free amino group of CWP was higher, average peptide length and molecular weight were similar in both fractions. AWP liposomes had slightly lower encapsulation efficiency than encapsulated CWP. Encapsulated CWP had larger mean particle diameter and higher polydispersity index. However, there was no apparent effect of peptide net charge on liposome surface charge (ζ-potential). FTIR spectra of the CWP- and AWP-loaded liposomes were similar and showed peptide interaction with the liposome phosphate groups. The peptide net charge did not appear to influence their distribution in different regions of the nanocapsules. The EE and physicochemical properties of the liposomes may be influenced by a combination of peptide net charge, homogeneity, and surface hydrophobicity. These findings are relevant to developing efficient liposomal systems for bioactive peptide delivery. Graphical abstract: Highlights: Encapsulation efficiency of charged whey peptide fractions within liposomes was over 85%. Peptide net charge affected encapsulation efficiency and liposome size. Electrical charge of the liposomes was not affected by the peptide net charges. Peptide charge did not influence their distribution in the different regions of the liposomes. The findings will facilitate nanovescicle design for delivering charged bioactive peptides.